Radiographic Evaluation of Isolated Continuous Compression Staples for Midfoot and Chopart Arthrodesis. Issue 1 (January 2022) - Schweser, Kyle M.; Horner, Kevin; Fiala, Kyle; Summerhays, Benjamin
Category: Midfoot/Forefoot; Hindfoot Introduction/Purpose: The use of continuous compression implants (nitinol staples) in orthopaedic surgery has increased secondary to advances in metal alloy engineering. Biomechanical studies provide useful data supporting the theoretical use of nitinol staples in the foot and ankle; however, clinical data is limited. There are several advantages of nitinol staples, including a lower profile when compared to traditional fixation methods. They are easy to apply and take up a smaller footprint than most plating techniques, thus decreasing surgical time and dissection. Additionally, continuous compression across the fusion site is maintained, as opposed to lag screw fixation. The purpose of this study was to determine the overall effectiveness, clinically and radiographically, of continuous compression implants (nitinol staples) to achieve stable arthrodesis in the midfoot and Chopart joints. Methods: A retrospective chart review was performed on 18 patients (37 joints) who underwent arthrodesis of the midfoot or Chopart joints utilizing isolated continuous compression implants between January 2017-December 2019. The primary outcome variable was radiographic evidence of arthrodesis on x-ray. X-rays were independently reviewed by three board-certified foot and ankle surgeons. All investigators were blinded towards the x-rays, and x-rays were randomized in terms of timing from surgery. Each investigator reviewed digital radiographs independently and recorded their radiographic finding responses. Joints were deemed fused if greater than 50% of the joint contained bridging bone radiographically. A partial fusion was defined as some bridging bone, but less than 50% of the joint involved, and nonunion was defined as no arthrodesis seen radiographically, broken hardware, or loss of reduction. Smokers and diabetics represented 22% and 11% of the patient population, respectively. Results: Radiographic union was seen in 88.8% of TMT joints (16/18) and 83.3% of midfoot joints overall (20/24). Nonunion rates were 11.2% (2/18) and 16.6% (4/24) respectively. Diabetes was associated for 50% (3/6) of nonunions. Mean time-to-fusion for TMT joints was 60 days. In Chopart joint fusions, nonunion rate was 46% (6/13), 2/6 (33%) were smokers. Overall, diabetes and smoking was associated with 40% (4/10) of all nonunion cases. TMT joint fusions had a significantly lower proportion of nonunion rates than hindfoot fusions (p=0.043). Radiographic Interobserver reliability was moderately strong between reviewers. Clinically, Chopart joint fusion patients had a significantly longer time course to weight bearing (p = 0.028). 8% (4/50) had broken hardware, all in nonunions, 75% (3/4) occurring in Chopart joints. Conclusion: Isolated nitinol staples are a viable option for midfoot arthrodesis, especially TMT joints, and offer multiple advantages when compared to traditional fixation methods. Staples are lower profile, eliminating hardware irritation and potential secondary surgeries, are technically less demanding, and time of application is decreased when compared to other methods. They offer the benefit of continuous compression of the fusion site, as well, and are rigid enough to maintain reduction. However, Chopart joints may require a more rigid fixation than CCI staples can provide, given the higher nonunion rate, and caution should be exercised in diabetics and smokers.